A Micro-Political Analysis of Local Governance in Nigeria: The Case of Irepodun Local Government Authority - Akinrinde, Olawale Olufemi; Adebisi, Ademola Mubarak (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
The study examined local government autonomy and local government service delivery in Nigeria. the study discovered that, Nigerian local government needs to be autonomous in the discharge of its statutory responsibility, if ongoing agitation for local government autonomy from different quarters in Nigeria is given an approval, this will strengthen local government’s service delivery. The study discovered that some states in Nigeria oppose local government autonomy due to political and economic considerations. The study further revealed that Irepodun local government (the micro-case study) in Nigeria is not totally autonomous. Although, local governance is transparent and accountable in Irepodun Local Government, especially in the identification, formulation and execution of its projects, Irepodun local government authority has a huge financial challenge in carrying out service delivery. The study therefore recommends that; the state joint local government account should be abolished from the Nigerian constitution to enable allocation of funds directly to the local governments from Federation account. they should also put a stop to the persistence deduction from the monthly allocation of local governments. Again, states should henceforth be made to remit regularly the constitutional 10% of their internally generated revenue to the local government authorities. Irepodun local government and other local government authorities in Nigeria emplace more efforts on sustainable wealth creation rather than depending solely on the grants from the federal and state governments.

W artykule przeanalizowano autonomię samorządu lokalnego i świadczeń usług samorządowych w Nigerii. Badanie wykazało, że nigeryjski samorząd lokalny musi być niezależny w wykonywaniu swoich ustawowych obowiązków. Czynnikiem wzmacniającym świadczenie usług przez samorząd lokalny może być skuteczna agitacja różnych środowisk na rzecz niezależności samorządu Nigerii. Analiza wykazała, że niektóre stany w Nigerii sprzeciwiają się autonomii samorządów lokalnych ze względów politycznych i ekonomicznych. Wykazano ponadto, że samorząd lokalny Irepodun (studium przypadku mikro) w Nigerii nie jest całkowicie autonomiczny. Chociaż samorząd lokalny w Irepodun jest przejrzysty i odpowiedzialny, zwłaszcza w zakresie identyfikacji, formułowania i realizacji swoich projektów. Musi on sprostać ogromnemu wyzwaniu finansowemu w realizacji świadczenia usług. W związku z tym badanie rekomenduje, usunięcie z konstytucji Nigerii zapisu dotyczącego wspólnego konta samorządowego, aby umożliwić alokację środków bezpośrednio do samorządów z konta Federacji. Należy zmusić państwo do regularnego przekazywania władzom samorządowym konstytucyjnych 10% ich wewnętrznie wytworzonych dochodów. Samorząd lokalny Irepodun i inne władze samorządowe w Nigerii powinny podjąć więcej wysiłków na rzecz trwałego tworzenia dobrobytu, zamiast polegać wyłącznie na dotacjach od rządu federalnego i władz stanowych.
Analiza mikropolityczna samorządu lokalnego w Nigerii: przypadek władz samorządowych Irepodun
Keywords: local governance; local government autonomy; service delivery; micro-political analysis; irepodun local government; Nigeria; samorząd lokalny; autonomia samorządu; świadczenie usług; analiza mikropolityczna; samorząd lokalny; Nigeria